Heart rate variability analysed by Poincaré plot in patients with metabolic syndrome - Kubičková, Alena; Kozumplík, Jiří; Nováková, Zuzana; Plachý, Martin; Jurák, Pavel; Lipoldová, Jolana (Journal of electrocardiology, 2015)
INTRODUCTION: The SD1 and SD2 indexes (standard deviations in two orthogonal directions of the Poincaré plot) carry similar information to the spectral density power of the high and low frequency bands but have the advantage of easier calculation and lesser stationarity dependence. METHODS: ECG signals from metabolic syndrome (MetS) and control group patients during tilt table test under controlled breathing (20 breaths/minute) were obtained. SD1, SD2, SDRR (standard deviation of RR intervals) and RMSSD (root mean square of successive differences of RR intervals) were evaluated for 31 control group and 33 MetS subjects. RESULTS: Statistically significant lower values were observed in MetS patients in supine position (SD1: p=0.03, SD2: p=0.002, SDRR: p=0.006, RMSSD: p=0.01) and during tilt (SD2: p=0.004, SDRR: p=0.007). CONCLUSION: SD1 and SD2 combining the advantages of time and frequency domain methods, distinguish successfully between MetS and control subjects.
Keywords: Diagnosis, Computer-Assisted; Sensitivity and Specificity; senzitivita a specificita; Oscillometry; Humans; Algorithms; diagnóza počítačová; Electrocardiography; Female; dospělí; Heart Rate; lidé; reprodukovatelnost výsledků; metabolický syndrom; Adult; ženské pohlaví; Male; srdeční frekvence; Reproducibility of Results; Metabolic Syndrome; srdeční arytmie; algoritmy; Arrhythmias, Cardiac; mužské pohlaví; oscilometrie; elektrokardiografie